Effectiveness of Women Subsidy Loan in Promoting Women Entrepreneurship in Banke District, Nepal - Khanal, Sugita; Khanal, Madhav Prasad (Mangal Research Journal, 2024)
In recognition of the significance of women's entrepreneurship in strengthening the nation's economy, the government of Nepal has implemented a program of offering subsidized loans. This study has been carried out with an objective of evaluating the effectiveness of women’s subsidy loan program in promoting entrepreneurship among women in Banke district. The research utilizes a descriptive approach to examine the impact of such financial interventions made by the government on women's entrepreneurial activity in the region. A survey method was employed to select 60 women entrepreneurs as the sample of the study who have utilized subsidy loans provided by five commercial banks in Banke. A convenient method for sampling was employed for selecting respondents, facilitating accessibility and mitigating resource constraints and the data were gathered using a detailed questionnaire. The study concluded that the majority of the respondents (66.7%) borrowed a loan ranging between 13-15 Lakh of which 25% of the respondents invested in stocks. Many respondents (55%), reported earning a profit ranging from 3 to 6 lakh. There exists a moderate positive correlation between the initial investment amount and the level of profit. Moreover, the loan has facilitated the women in earning greater revenues, creating employment opportunities for others, and extending the scale of their firm.